One-pot synthesis of tricyclo-1, 4-benzoxazines via visible-light photoredox catalysis in continuous flow. Issue 14 (5th April 2017) - Wu, Guolin; Lv, Tingting; Mo, Wenhui; Yang, Xiping; Gao, Yu; Chen, Haijun
Graphical abstract: Highlights: A facile continuous-flow method to access tricyclo-1, 4-benzoxazines. The reaction was efficiently achieved at ambient temperature. The procedure could be easily handled and scaled up. Enabling construction of a focused compound library. Abstract: A facile one-pot synthesis of tricyclo-1, 4-benzoxazines has been developed via metal-free intramolecular cyclization of indole derivates. These reactions were efficiently achieved at ambient temperature by using visible-light photoredox catalysis in continuous flow. This directed intramolecular cyclization could be easily handled and scaled up in an open flask, enabling construction of a focused compound library for further pharmacological evaluation.